Suatu Tinjauan Kriminologis Terhadap Kasus Delinkuensi Anak: Analisis Faktor, Teori, dan Sanksi - Rantri Ridho Salma (Jurnal Kajian Ilmiah, 2023)
The involvement of a child in delinquent behavior is a product of the ineffectiveness of a system and social structure to protect the child. This certainly has an impact on the life of the child in the future. There are many elements that must be considered, so it is important to understand the phenomenon of child delinquency in depth. Therefore, this article seeks to specifically discuss a case of child delinquency, namely a case that involves insults, hate speech, and threats made by 16 year olds on social media. Through the case, this article aims to: 1) categorize the forms of violations in related cases; 2) describe the factors causing the vulnerability of the related behavior; 3) describe the theoretical explanation of the behavior in the case concerned; and 4) describe the appropriateness of sanctions given to children in related cases. By using the literature study method, this article uses a qualitative approach, in the form of a case study through a criminological theoretical review. The results of the analysis show that: 1) the form of violation in the related case is an act of delinquency; 2) social factors identified in the case include family, school, media, and peers; 3) the theory of neutralization techniques can explain how children are able to carry out these delinquent actions; and 4) sanctions to return the perpetrators to their parents are appropriate.